Use of Portable Air Purification Systems to Eliminate Aerosol Particles from Patient Rooms - Dominic Dellweg; Gerhard Scheuch; Thomas Voshaar; Dieter Köhler (Aerosol and Air Quality Research)
Abstract SARS-CoV-2 is mainly transmitted via airborne aerosols. We determined the efficacy of two different indoor air-purification systems and compared them to conventional measures of room ventilation. Radioactive particles with a mass median aerodynamic diameter of 0.6 ± 0.4 µm were nebulized from the head position of a simulated patient inside a 38 m3 measuring room. Air samples were drawn using an artificial lung from outside the room from the head and belly position of the simulated patient. The radioactivity from these air samples was determined in % of the minute-by-minute release of aerosol by the simulated patient. The samples were taken with the windows closed, with the windows open and with two different air purification systems in different locations. Opening the windows while the fan was working did not reduce the cumulative mass of sampled particles during ongoing nebulization. Only the more powerful air purifier was able to decrease cumulative sampled radioactivity almost to zero when positioned close to the emitting particle source. We observed air-turbulences caused by the air intake of the air purifier resulting in regional particle concentration peaks. Measurements and calculations demonstrate that indoor air purification systems can be effective measures to eliminate airborne particles. The air cleaning capacity of the system must be matched to the room size and the air intake of the units should be positioned close to the particle source.